Plastic Surgery Practice during COVID Times - Deepak Bhaskaran; Aswathy Chandran; Sheeja Rajan T.M (Indian Journal of Plastic Surgery)
Introduction COVID-19 has affected plastic surgeons like never before. We conducted an all-India survey to find how the practice was affected among public/private sector, reconstructive/aesthetic practice, and consultants/residents. We have proposed some solutions to the identified problems, which are supported by previous literature. Methods A survey framed in Google forms was circulated through WhatsApp and emails in August 2020. Closed and semiopen questions regarding changes in personal and professional lives, coping strategies adopted, and open questions for suggestions in improving practice, academics and measures to tackle the pandemic were included. Responses were collected in an Excel sheet and analysis done using SPSS software. Results A total of 220 consented responses were obtained. Public hospital practitioners had to bear the COVID-related administrative as well as executive works, especially residents, which led to anxiety, family concern, burnout, and concern about the loss of skills and academics. Patient interaction was also reduced. Aesthetic surgeons bore more financial loss. Conclusions Plastic surgeons in India faced decrease in caseload, financial loss, COVID-related duties, workload for residents, reduced academics, family and mental health problems, difficulty with personal protection equipment (PPE) during surgeries, and queries from patients. These can be solved by doing cases within the limits of protocols and safety, pooling public and private sector for COVID duties, rotating residents' groups to reduce workload, using telemedicine for academics and patient consultations, and providing social support groups to surgeons.